Data Structures Implementation of the Protocol Step-NC at CNC Machines Programming - Cubonova, Nadezda; Kuric, Ivan (Communications - Scientific letters of the University of Zilina, 2014)
Standard STEP-NC (ISO 14649) presents a new model for data transmission between CAD/CAM systems and CNC machines. This standard eliminates the shortcomings of the standard G-code and provides new possibilities in their management. At the Department of Automation and Production Systems, Faculty of Mechanical Engineering, University of Zilina in the framework of the research activities was solved a project for the implementation options of STEP-NC format by programming of CNC machines. This paper presents the results of research solutions which focused mainly on the analysis of standard STEP-NC, a methodology on the model data according to the standard STEP-NC using the EXPRESS language as well as the creation of software for the transformation of STEP-NC data - „TERMINAL STEP NC“. The software has been verified in the transmission of STEP-NC data to a particular CNC machine control system. Transfer of STEP-NC data applications gives the possibility of verifying the implementation of the new standard in older types of CNC machines.